Signaling pathways in hair aging - Liang, Aishi; Fang, Yingshan; Ye, Lan; Meng, Jianda; Wang, Xusheng; Chen, Jinsong; Xu, Xuejuan (Frontiers in Cell and Developmental Biology, 2023)
Hair follicle (HF) homeostasis is regulated by various signaling pathways.Disruption of such homeostasis leads to HF disorders, such as alopecia, pigment loss, and hair aging, which is causing severe health problems and aesthetic concerns. Among these disorders, hair aging is characterized by hair graying, hair loss, hair follicle miniaturization (HFM), and structural changes to the hair shaft. Hair aging occurs under physiological conditions, while premature hair aging is often associated with certain pathological conditions. Numerous investigations have been made to determine the mechanisms and explore treatments to prevent hair aging. The most well-known hypotheses about hair aging include oxidative stress, hormonal disorders, inflammation, as well as DNA damage and repair defects. Ultimately, these factors pose threats to HF cells, especially stem cells such as hair follicle stem cells, melanocyte stem cells, and mesenchymal stem cells, which hamper hair regeneration and pigmentation.Here, we summarize previous studies investigating the above mechanisms and the existing therapeutic methods for hair aging. We also provide insights into hair aging research and discuss the limitations and outlook.